The Women Representation Policy and its Effect to Women Political Participation in Jember, Indonesia - Ria Angin; Hary Yuswadi; Himawan Bayu Patriadi; Nur Dyah Gianawati (Otoritas : Jurnal Ilmu Pemerintahan, 2018)
The journey of the Indonesian government in implementing women representation policy has evolved. In the election of 2004,women representation policies have not mentioned the target of achievement for political parties. The policy only states that political parties are expected to implement gender equality in nominating candidates. Then in the year of  2009 election, the government had changed  the policy clause, and  states the percentage that must be achieved by political parties. However,  in 2004 and 2009 election only a few political parties,  implemented the policy. Yet, the  policy, which is implemented, in the 2014 election has changed. The clause of the policy became more distinct, for it contains sanctions which are applicable to any political parties that are not implementing the policy. The present study yielding that the more distinct the policy, the more likely it would be complied by all participating political parties. The effect of the complying political parties would be the increase of women participation in politics as candidates of legislatives.